Assessment of body mass index (BMI) and its association with nutritional knowledge and selected lifestyle-related behaviors in adults - Nowobilska-Luberda, Aleksandra; Wacławik-Kapłon, Emilia (Polish Journal of Public Health, 2026)
Introduction. Body mass index (BMI) is a widely used indirect indicator of nutritional status in adults, although it does not reflect body composition. The relationships between BMI, nutritional knowledge and lifestyle factors remain inconclusive. Aim. The aim of the study was to assess BMI and its associations with nutritional knowledge and selected lifestyle factors in adults. Materials and methods. The study included 107 adults aged 20–63 years from Poland. Data were collected using an anonymous online questionnaire based on selected sections of the KomPAN® questionnaire. BMI was calculated from self-reported body weight and height according to World Health Organization criteria. Nutritional knowledge was assessed using 13 selected questions. Correlation analyses were performed using Spearman’s rank and Pearson’s coefficients (p < 0.05). Results. No significant associations were found between BMI and overall nutritional knowledge or selected unhealthy dietary behaviors. A significant weak negative correlation was observed between BMI and sleep duration (ρ = −0.21; p = 0.030). In gender-stratified analyses, a positive association between BMI and nutritional knowledge was observed only in women. Conclusions. Sleep duration was the only lifestyle factor significantly associated with BMI. Nutritional knowledge alone was not related to BMI, suggesting that knowledge may not translate into a healthier body weight. The findings emphasize the role of sleep hygiene in obesity prevention.